Numerical accuracy of bisection method - Srivastava, R B; Dixit, Narendra Deo (International Multidisciplinary Research Journal, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> A computer program in C++ language has been developed to calculate square roots of numbers from 1 to 25 in interval [0, 6] using bisection method. Accuracy of bisection method has been found out in each calculation. Lowest accuracy has been observed in the calculation of square root of 1 in the interval [0, 6] and percentage error is equal to 0.000381469700. Highest accuracy has been observed in the evaluation of square root of 13 in the interval [0, 6] and percentage error is equal to 0.000000905160. Average percentage error of bisection method in the calculation of square roots of natural numbers from 1 to 25 has been found to be 0.000041549568 which indicates that the accuracy of bisection method can be increased by reducing tolerance value.